2016
DOI: 10.1371/journal.pone.0146797
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Brain Levels of Vitamin B12 in Aging, Autism and Schizophrenia

Abstract: Many studies indicate a crucial role for the vitamin B12 and folate-dependent enzyme methionine synthase (MS) in brain development and function, but vitamin B12 status in the brain across the lifespan has not been previously investigated. Vitamin B12 (cobalamin, Cbl) exists in multiple forms, including methylcobalamin (MeCbl) and adenosylcobalamin (AdoCbl), serving as cofactors for MS and methylmalonylCoA mutase, respectively. We measured levels of five Cbl species in postmortem human frontal cortex of 43 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(100 citation statements)
references
References 87 publications
4
93
0
3
Order By: Relevance
“…We have previously shown that decreased GSH levels and elevated oxidative stress can subsequently result in altered epigenetic changes, specifically DNA methylation levels via the vitamin-B12-dependent enzyme methionine synthase [29]. In agreement, we observed that sleep deprivation increased the global DNA methylation levels.…”
Section: Discussionsupporting
confidence: 88%
“…We have previously shown that decreased GSH levels and elevated oxidative stress can subsequently result in altered epigenetic changes, specifically DNA methylation levels via the vitamin-B12-dependent enzyme methionine synthase [29]. In agreement, we observed that sleep deprivation increased the global DNA methylation levels.…”
Section: Discussionsupporting
confidence: 88%
“…Subcutaneous methyl‐B12 in children with autism has shown improvement with the clinician‐rated score on the Clinical Global Impressions Scale, and was positively correlated with increases in plasma methionine, and decreases in S‐adenosyl‐1‐HCy and improvement in the S‐adenosylmethionine‐to‐S‐adenosyl‐1‐HCy ratio . This is consistent with the observation that the levels of B12 were threefold lower in the brains of autistic subjects compared with age‐matched controls ( n = 12) …”
Section: Future Directionssupporting
confidence: 85%
“…Subsequently vitamin B 12 deficiency leads to elevated homocysteine, and impaired folate metabolism [306]. Decreased vitamin B 12 concentrations have been demonstrated in postmortem human frontal cortex from patients with autism and schizophrenia, as well as to decline with age (range from 19 weeks pregnancy to 80 years) [307].…”
Section: The Role Of Trace Elements and Micronutrients In Agingmentioning
confidence: 99%